The Doctrine of Logos Within Ibn ‘Arabi Mystical Philosophy - Muzairi Muzairi; Novian Widiadharma (UIN Sunan Kalijaga Yogyakarta, 2017)
There are no less than twenty-two terms which Ibn ‘Arabi uses to designate what one might call a Mohammedan Logos. References to these terms, with explanations, will be given later. The reason, why we find Ibn‘Arabi using such a large collection of terms for one thing, is twofold. In the first place, it is due to the fact that he derived his material from so many divergent sources, preserving, so far as possible, the terminology of each source. Here, e.g., he is using terms borrowed from Sufis, scholastic theologians, Neo-platonists, the Qur’an and so on. Secondly, his pantheism enables him to use the name of anything for the One Reality which is the ultimate ground of all things. The terms to below refer to different aspects of the One Reality which is now regarded as the Logos.[Tidak kurang dari sekitar 22 istilah yang digunakan oleh Ibn ‘Arabi untuk merujuk apa yang disebut sebagai “logos Muhammad”. Beberapa referensi bagi istilah tersebut dengan penjelasannya akan dijelaskan berikutnya. Terdapat dua alasan utama yang menjadikan Ibn ‘Araby menggunakan puluhan istilah untuk menyebut hal yang sama. Pertama, dikarenakan adanya fakta bahwa ia mengambil seluruh material dari berbagai macam sumber dan sebisa mungkin mempertahankan istilah dari masing-masing sumber. Dalam hal ini, ia meminjam istilah dari kelompok sufi, teolog skolastik, neo-platonis, al-Qur ’an dan yang lainnya. Kedua, panteisme-nya memungkinkan untuk memakai beragam nama sesuatu bagi satu realitas yang menjadi pusat dari segala sesuatu. Istilah-istilah yang begitu banyak merupakan aspek-aspek yang berbeda dari Realitas Yang Satu yang kini dipandang sebagai Logos.]